Disability and health outcomes - from a cohort of people on long-term anti-retroviral therapy - Hellen Myezwa; Jill Hanass-Hancock; Adedayo Tunde Ajidahun; Bradley Carpenter (Taylor & Francis Group, 2018)
Human-immunodeficiency virus (HIV)/Acquired immunodeficiency Syndrome (AIDS) remains a major health problem in South Africa - even after two decades since the introduction of antiretroviral therapy (ART). Long-term survival with HIV is associated with new health-related issues and a risk of functional limitation/disability. The aim of this study was to assess functional limitation associated with HIV/AIDS among people living with HIV (PLHIV) in South Africa. This study is a cross-sectional survey using a cohort in an urban area in Gauteng province, South Africa. Data were collected using questionnaires through an interview process. The information collected included aspects such as demographics, livelihood, the state of mental and physical health, adherence and disability. A total of 1044 participants with an average age of 42 ± 12 years were included in the study, with 51.9% of the participants reporting functional limitations (WHODAS ≥ 2). These were reported mainly in the domains of participation (40.2%) and mobility (38.7%). In addition, adherence to ART, symptoms of poor physical health and depression were strongly associated with their functional limitations/disability. HIV as a chronic disease is associated with functional limitations that are not adequately addressed and pose a risk of long-term disability and negative adherence outcomes. Therefore, wellness for PLHIV/AIDS needs to include interventions that can prevent and manage disability.